Supressão temporária do crescimento folicular ovariano em ovelha pela administraçao continuada de deslorelina na forma injetável ou implante de liberação controlada - Scagion, Luiz Fernando Salgado [UNESP] (2015)
The objective is to comparatively study the 100μg deslorelin serial administration effects front implantation of sustained release deslorelin (4.7 mg) on the temporary suppression of ovarian follicular growth in Bergamacia ewe aiming the application in biotechnology for the control of ovulation. After an adaptation period and monitoring of cyclicity, they had estrus synchronized with the second use intravaginal device Eazi-Breed CIDR® (0.33g progesterone) for 12 days and a single intramuscular injection, of eCG 350UI concurrently with the removal of the device. Blood samples were collected for confirmation of ovulation and cyclicality by measuring plasma progesterone being considered with luteal activity those animals with values equal or higher than 1 ng / mL. Elapsed six days of ovulation females was then be randomly divided into four groups: G0 (Control): untreated animals; G1 (DES 48h); animals subjected to intramuscular injections of 100μg deslorelin every 48 hours for seven days; G2 (DES 72h) animals subjected to intramuscular injections of 100μg deslorelin every 72 hours for seven days; and G3 (implant): animals with subcutaneous implant containing 4.7 mg deslorelin that remained for seven days. During the specific treatment period of each group (seven days), the animals ovaries was monitored by ultrasound to establish the suppression of follicular growth. And the follicles present in the ovaries classified into small, with a diameter of 2 to 2.9 mm, medium, with a diameter of 3 to 4.4 mm and large diameter ≥4.5mm. Ovarian ultrasound monitoring was maintained after completion of treatment, until 100% of the sheep retake the follicular activity. The follicular population was compared in the groups and between the groups during the treatment period. The G0 (Control) did not differ (p> 0.05) between the follicles classes wherein the post-synchronization elapsed time did not allow to characterize the typical pattern in ...